Design and manufacturing of 15 DOF myoelectric controlled prosthetic hand - Tasar, Beyda; Gulten, Arif; Yakut, Oguz (Pamukkale Univ, 2020)
This study's main purpose is to manufacture a low-cost, highly functional, myoelectric signal-controlled prosthetic hand for amputees in developing countries below a certain economic level. In this study, a prosthetic hand with five fingers was modeled on 15-degree freedom, and an independent joint movement was achieved through the use of a separate motor actuator for each joint in the fingers. The hand of the prosthetic can therefore keep the objects in the best possible way. The prosthetic was produced by hand using PLA material on a 3D printer to reduce cost. Bioelectric signals provide the human-prosthetic hand interaction, i.e. identification of the form of hand gesture. With 97 percent progress, the classification of a human hand with the SVM algorithm has been achieved. The prosthetic hand's total cost is US$ 450. The hand was compared in terms of qualitative and quantitative performance metrics with other high-priced rivals and the findings were interpreted.
Keywords: prosthetic hand; 3D Manufacturing; PLA; Myo-controlled-hand; EMG; Supported vector machine; Gesture recognition